Sundanese Philosophy of Silih Asah, Asih, Asuh: A Picture of Social Welfare Influenced by Traditional Belief and Ethnocentrism - Ibad, M. Choirul; Ubaidillah, Fauzul Adim; Widiatmoko, Sigit (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2026)
The traditional values of the Sundanese are reflected in the philosophy of silih asah, silih asih, silih asuh, which forms the basis of social relations in the society. Therefore, this study aimed to examine the influence of traditional and ethnocentric beliefs on the social welfare of the Sundanese. The social welfare reflected in the cultural forms of the Sundanese was also examined using a mixed-methods design with a sequential explanation strategy. A total of 375 respondents were selected through a purposive sampling method with the help of a Google Form. The measurement instruments consisted of traditional belief, ethnocentrism, and social welfare that had been adjusted to the study context. The results of the study showed a positive and significant influence of the traditional beliefs of the Sundanese on social welfare. There was also a negative and significant influence of the Sundanese ethnocentrism on social welfare. The results of this study also showed that social welfare in the Sundanese was reflected in several cultural tradition values from the philosophy of silih asah, silih asih, silih asuh.